(untitled) - Lê, Văn Lành (Cần Thơ, 2018)
This thesis introduce about investigation into students' attitudies towards "test-preparation teaching" in their TOEIC-ORIENTED courses: a case in the Mekon delta.
Keywords: English language,Tiếng Anh; Study and teaching,Học và dạy học